PENGARUH PENGETAHUAN AKUNTANSI, PENGGUNAAN E-COMMERCE DAN SISTEM INFORMASI AKUNTANSI TERHADAP EFEKTIVITAS KINERJA KEUANGAN UMKM DI KABUPATEN PONOROGO - Takesya Avrielda Tirta Zetilla; Ika Farida Ulfah; Iin Wijayanti (JAPP: JURNAL AKUNTANSI, PERPAJAKAN DAN PORTOFOLIO, 2026)
This study aims to examine the extent to which accounting knowledge, e-commerce use, and accounting information systems improve the effectiveness of MSMEs' financial performance in Ponorogo Regency. In MSME management, these factors are considered crucial to ensure efficiency and accountability of profit and loss, especially in small and medium enterprises. This study uses a quantitative approach by distributing questionnaires to MSME owners or actors in Ponorogo Regency purposively. Data analysis in the study was conducted using multiple linear regression techniques. The results show that, both partially and simultaneously, accounting knowledge and e-commerce use have a positive and significant influence on the effectiveness of financial performance. Meanwhile, the accounting information system variable shows a significant negative influence on the effectiveness of financial performance in the context of MSMEs.